Estudo comparativo das alterações metabólicas induzidas por hiperplasia fiboadenomatosa da próstata versus adenocarcinoma próstatico em humanos - Pinto, Francisco Salvio Cavalcante (1996)
There is a lack of information on the utilization of metabolites by various human malignant tumors in vivo. In this present work blood and prostatic tissue concentrations of pyruvate, lactate, glutamate, glucose-6-phosphate, glucose, acetoacetate, 3-hydroxybutyrate, ketone bodies, and the acetoacetate/3-hydroxybutyrate ratio which is an indicator of the mitochondrial redox State, were measured in vivo in 19 patients with prostatic adenoma and compared to those concentrations obtained in 16 patients with prostatic adenocarcinoma. Two mililiters of blood and approximately one gram of prostatic tissue were sampled from patients who underwenteitheropen and transurethral prostatectomy. Blood samples were deproteinized with 10% percloric acid and tissue samples were freeze-clamped with liquid nitrogen and then neutralized and assayed by enzymatic methods. There were no differences in blood or tissue concentrations of metabolites when the procedure was either open prostatectomy or transurethral prostatectomy. However, the acetoacetate/3-hydroxybutyrate ratio was significantly elevated in the prostatic tissue of patients with adenocarcinoma as compared to those with adenoma suggesting a higher redox mitochondrial State in malignant tumors as compared to hyperplasic benign tumors. The elevation of this ratio also occurred in the blood of câncer patients (more than 10 times) and may raise the possibility of using it as a blood test to differentiate patients with adenoma from those with adenocarcinoma of the prostate gland.